Studi Komparatif Konsep Perdamaian (Ash-Shulhu) dalam Kitab Bulughul Maram dan Implementasinya pada Akad Kontemporer - Nuranisya, Siti; Najib, Moh (Indonesian Journal of Islamic Jurisprudence, Economic and Legal Theory, 2025)
This research aims to analyze the legal standing and mechanisms of settlement (ash-shulhu) in muamalah (Islamic transactions) based on the perspective of hadith ahkam (legal hadiths). Amidst the complexity of modern economic disputes, peace settlements often emerge as a more effective solution than court litigation. This study employs a qualitative method with a library research approach and thematic analysis (maudhu’i) of hadiths related to reconciliation, specifically the hadith "Ash-shulhu jaizun baina al-muslimin" (settlement is permissible among Muslims). The results indicate that hadith ahkam provides strong legitimacy for ash-shulhu as a legal instrument to resolve material disputes, provided it does not permit what is forbidden or forbid what is permitted. Practically, the concept of ash-shulhu in hadith is highly relevant to modern Alternative Dispute Resolution (ADR) principles, which emphasize justice, mutual consent, and collective benefit in economic transactions.